Спрежение на слабите глаголи с основа на двойна сонорна (назална и латерална) съгласна в норвежки (букмол) и датски - Bakalova, Maria (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2021)
The present article compares the conjungation patterns of weak verbs ending in stem-final geminate sonorant (nasal and lateral) consonants -/m(ː)/-, -/n(ː)/-, /ŋ(ː)/-, -/l(ː)/- in Norwegian (Bokmål) and Danish. A corpus study is conducted whose results show that the phonologically conditioned generalization of the 1st conjugation pattern in verb stems containing a short vowel is prevalent in both languages also when the stem-final consonant is a nasal or lateral. Danish, however, demonstrates a stronger prevalence of this generalization than Norwegian, which leads to some cases of differing conjungation of cognate weak verbs in these two languages.
Keywords: Norwegian; Danish; weak verbs; conjugation; sonorant consonants